Metadata Model for Engineering of Sustainable Products in Value Creation Networks - Gräßler, Iris; Rarbach, Sven; Pottebaum, Jens; Luessen, Florian; Hoffmann, Joerg (Procedia CIRP)

Metadata-based assessment of Data Quality for Engineering of Sustainable Products - Gräßler, Iris; Rarbach, Sven; Pottebaum, Jens; Hoffmann, Joerg (Procedia CIRP)

„transMINT4.0“ – MINT-Bildung stärken durch die Ein- bindung außerschulischer Lernorte am Übergang von der Primar- zur Sekundarstufe - Blumberg, Eva; Wenzel, Annkathrin; Schulze, Jan Roland; Reckmann, Eileen; Puppe, Ricardo; Crummenerl, Lena Luise; Temmen, Katrin (GDSU-Journal)

Service through communication—Conceptualizing service systems with Luhmann’s systems theory - Beverungen, Daniel; Poeppelbuss, Jens; Hemmrich, Simon; Iqbal, Taskeen (Electronic Markets)
Service research has evolved into an interdisciplinary research field that bridges diverse disciplines, including information systems (IS) and marketing. Nearly two decades ago, the service system concept was introduced as a foundational abstraction in service research, drawing on ideas from the service-dominant logic (S-D logic) of marketing. Despite its widespread adoption in service research, particularly in the IS discipline, the service system concept lacks a solid theoretical foundation. This has resulted in conceptual ambiguity and overlap with related constructs, such as service ecosystems. Moreover, it has largely remained a static analytical lens, insufficiently capturing dynamic service phenomena, including value co-creation and co-destruction, as well as the emergence of institutional arrangements. To address these limitations, we propose Luhmann’s systems theory (LST) as a robust framework for conceptualizing service systems as autopoietic (self-creating) systems, in which communication serves as the fundamental mechanism that drives value co-creation. We derive five theoretical propositions from this re-conceptualization that clarify conceptual ambiguity and allow researchers to explore dynamic service phenomena in greater depth. Given LST’s general approach, our conceptualization provides a theoretically grounded, interdisciplinary foundation for advancing service research.
Keywords: Service system; Service ecosystem; Systems theory; Service research

Bridging chemistry and Gaussian boson sampling: a photonic hierarchy of approximations for molecular vibronic spectra - Eickmann, Jan-Lucas; Luo, Kai-Hong; Roiz, Mikhail; Lammers, Jonas; Atzeni, Simone; Pandey, Cheeranjiv; Lütkewitte, Florian; Shirazi, Reza G.; Schlue, Fabian; Brecht, Benjamin; Rybkin, Vladimir V.; Stefszky, Michael; et al. (npj Quantum Information)
Simulating vibronic spectra is a central task in physical chemistry, offering insight into important properties of molecules. Recently, it has been experimentally demonstrated that photonic platforms based on Gaussian boson sampling (GBS) are capable of performing these simulations. However, whether an actual GBS approach is required depends on the molecule under investigation. To develop a better understanding on the requirements for simulating vibronic spectra, we explore connections between theoretical approximations in physical chemistry and their photonic counterparts. Mapping these approximations into photonics, we show that for certain molecules the GBS approach is unnecessary. We place special emphasis on the linear coupling approximation, which in photonics corresponds to sampling from multiple coherent states. By implementing this approach in experiments, we demonstrate improved similarities over previously reported GBS results for formic acid and identify the particular attributes that a molecule must exhibit for this, and other approximations, to be valid. These results highlight the importance in forming deeper connections between traditional methods and photonic approaches.

Dimensions of Heuristic Use in Mathematical Problem Solving: Evidence from Early Secondary School Students - Herold-Blasius, Raja; Kleinschmidt, Hannah; Ziller, Conrad (Journal für Mathematik-Didaktik)
Mathematical problem solving is a highly complex competence that needs to be supported throughout the learning process. This study examines the role of problem-solving heuristics among 73 sixth-grade students in a German secondary school (Gesamtschule). Specifically, we focus on the empirical relationship between the occurrence of heuristics, their suitability, and application, as well as their contribution to problem-solving success. To this end, we developed a heuristic training that introduced strategy keys (heuristic aid cards) accompanied by explanatory videos. By leveraging variations in the successful application of the heuristics between students and across multiple sessions (73 students in 4 training situations and 3 problems in a final test), we discover from regression models with student and task-fixed effects that a successful use of heuristics (i.e., an heuristic occurred, that heuristic had a high suitability regarding the problem, and it was applied correctly) leads to more successful mathematical problem solving. Regarding the underlying mechanism, we find that all dimensions of heuristic use (occurrence, suitability, and application of heuristics) are positively related to problem-solving success. When comparing the predictive capacity of all three aspects, we identified the correct application of heuristics as particularly conducive for better problem-solving success. In comparing the group of students with high to those with low initial math competence, we find no significant differences in the relationship between heuristic use and problemsolving success across achievement groups. Our results emphasize the crucial role of heuristic application in mathematical problem solving, which generally benefits students regardless of their overall math competence.

Adaptive Coaxial Concrete Rheometer (ACCR): Honest Rheological Measurements and Corrections - Jesinghausen, Steffen; Schmid, Hans-Joachim (Opus Fluidum Futurum—Rheology of Reactive, Multiscale, Multiphase Construction Materials)

Metamorphosen als Akte weiblicher Handlungsmacht in Texten von Brigitte Kronauer, Han Kang und Camilla Grudova - Öhlschläger, Claudia (Geschlecht und Macht (feministische studien))

Zu Fotografien der Berliner Künstlerin Cihan Çakmak - Öhlschläger, Claudia (Geschlecht und Macht (feministische studien))

Geschlecht und Macht - Öhlschläger, Claudia; Riegraf, Birgitt (Geschlecht und Macht (feministische studien))

Geschlecht und Macht (feministische studien)

„When does a man become a monster?“ Odysseus’ fluide Identität in Jorge Rivera-Herrans’ EPIC – The Musical - Peine, Sara (Wasser Wesen Wandel. Fluidität in (mehr-als-)literarischen Medien)

Thermodynamic Properties of Tetramethoxysilane - Fiedler, F.; Baumhögger, Elmar; Kruse, Simon; Lemmon, E. W.; Kasper, Tina; Thol, M. (International Journal of Thermophysics)
Abstract A fundamental equation of state for tetramethoxysilane (TMOS) is developed based on the available experimental data. In addition, new density and speed of sound measurements were performed specifically for this work to improve the database. Owing to the limited overall data set, additional thermodynamic properties were analyzed to support the fitting procedure and ensure physically consistent behavior. Modified representations of thermodynamic properties that are typically employed in the fitting procedure were introduced to facilitate the application of constraints. The resulting model provides a consistent description of the thermodynamic properties of TMOS.

Vom Hühner-Holocaust über die Öko-Diktatur zum Kulturkampf um die Currywurst. Korpuslinguistische Perspektiven auf ernährungsbezogene Politisierungen - Markewitz, Friedrich; Wilk, Nicole M. (Zeitschrift für Literaturwissenschaft undLinguistik)

120 Tage im 'SS Experiment Love Camp'. Zu Genretropen und -kontroversen im Nazisploitationfilm - Markewitz, Friedrich (Pop-Zeitschrift)

Art the Clown goes to Hollywood. Wenn transgressives Genrekino Mainstream wird - Markewitz, Friedrich (Pop-Zeitschrift)

(Nicht)Nutzung von KI-Werkzeugen in der Lehre: ein Reflexionspapier - Rohlfing, Katharina J.; Steinhardt, Isabel; Scharlau, Ingrid; Schaper, Niclas; Holtfreter, Susan; Biere, Lea; Grimminger, Angela; Schmidt, Rebecca; Festner, Dagmar Franziska; Schmidt, Rebekka; Buhl, Heike M.; Mindt, Ilka; et al.

Cost of debt for private firms revisited: voluntary audits as a reflection of risk - Ichev, Riste; Koren, Jernej; Kosi, Urska; Sitar Sustar, Katarina; Valentincic, Aljosa (International Review of Economics & Finance)
We examine the relation between voluntary audit and the cost of debt in private firms. We use a sample of 7420 small private firms operating in the period 2006-2022 that are not subject to mandatory audits. Firms self-select into voluntary audits because of the economic setting (e.g., ownership complexity, export, subsidiary status) or because firm fundamentals limit their access to financial debt. In the outcome analyses, we find that voluntary audits result in higher, rather than lower, interest rates with increases ranging from approximately 1.7 percentage points, but going higher depending on the exact specification. This effect is present regardless of the perceived audit quality (Big-4 vs. non-Big-4), consistent across auditor types. Audited firms’ earnings are less informative about future operating performance. Voluntary audits facilitate access to financial debt for high-risk firms. The price paid is reflected in higher interest rates for voluntary audits – firms with higher information/fundamental risk.

The Role of Stakeholders in CSR Reporting of Non-Listed Banks - Gulenko, Maryna; Kohlhase, Saskia; Kosi, Urska (Accounting in Europe)
We investigate the role of stakeholders in the CSR reporting of non-listed savings banks in Germany. They are established by municipal trustees and serve clients in their distinct operating area. Reporting discretion under the Non-Financial Reporting Directive may lead to variation in CSR reporting due to differences in sustainability interests of banks’ stakeholders and CSR governance (e.g. existence of a CSR manager). We document that the CSR reports and specific CSR dimensions are intensely associated with the existence of strong CSR governance and to a lesser extent with the interests of municipal trustees and bank clients. However, the associations with these stakeholders are predominantly present in banks with strong CSR governance. Our findings inform policy discussions about detailed CSR disclosure requirements (e.g. the European Sustainability Reporting Standards) and extension of reporting scope to firms with regional orientation and absence of typical shareholders.

Intertwining theory and practice: Design of planning phases in PD training to support effective teacher planning processes - Knaudt, Katharina; Herold-Blasius, Raja; Selter, Christoph (Proceedings of the Fourteenth Congress of the European Society for Research in Mathematics Education (CERME14)